Sdre control applied to an electromechanical pendulum excited by a non-ideal motor - Bueno, Atila Madureira [UNESP]; Tusset, Angelo Marcelo; Dos Santos, João Paulo Martins; Tsuchida, Masayoshi [UNESP]; Balthazar, José Manuel [UNESP] (ASME International, 2013)
The dynamical behavior of an electromechanical pendulum system is analyzed by means of the classical perturbation theory. A frequency response model of the system is obtained, and the number of unstable poles are determined with the Routh-Hurwitz criterion. Numerical simulations show that the system presents nonlinear behavior such as hysteresis, with hard and soft characteristics, and the Sommerfeld effect in the resonance region. In order to keep the oscillations of the electromechanical system in a pre-defined amplitude range a control strategy is designed. The SDRE control strategy is used considering two control signals, a feedback control that tracks the system to a desired periodic orbit, and a nonlinear feedforward control that holds the system to that desired periodic orbit. Additionally, the robustness of the control technique is tested for parametric uncertainties. Numerical simulations show the efficiency of the control strategy. Copyright © 2013 by ASME.